Following the COVID-19 Experience, Many Patients with Type 1 Diabetes Wish to Use Telemedicine in a Hybrid Format - Tal Schiller (MDPI AG, 2021)
Background: The COVID-19 pandemic has brought to light both challenges and unique opportunities regarding type 1 diabetes (T1D) management, including the usage of telemedicine platforms. Methods: This study was conducted in a tertiary hospital diabetes clinic. All consecutive T1D patients during March and June 2021 were asked to fill out a structured anonymous questionnaire that aimed to determine their preference regarding continuous use of a virtual platform. Results: In total, 126 T1D patients answered the questionnaire, of whom 51% were under the age of 40, half were men, half used insulin pumps, and 69% used continuous glucose monitoring. During the pandemic, the exposure of patients to virtual visits has grown about twofold, from 29% to 53%. Of the respondents, 49% expressed an interest in future usage of a virtual platform, but most of them preferred use in a hybrid manner. We found an association between preference to use telemedicine in the future and younger age, previous virtual platform experience, and confidence in being able to download data. Conclusions: Our data demonstrate that the COVID-19 experience has led to a growing interest of T1D patients in using the hybrid format of telemedicine. However, we still need to better understand who will benefit most from this platform and assess its cost-effectiveness and organization.